An assessment of the trophic ecology of escaped farmed rainbow trout (Oncorhynchus mykiss) in relation to native salmonids in the Westfjords, Iceland - Simmons, Olivia Meredith, 1994- (2018)
Verkefnið er lokað til 28.05.2019. Aquaculture is an important industry in the Westfjords, where one common species to farm is rainbow trout. Wherever there are fish farms, there tend to be fish escapes, and the Westfjords is no exception. The goal of this research was to compare the trophic ecology of escaped rainbow trout with two native salmonid species, Arctic charr (Salvelinus alpinus) and sea trout (Salmo trutta). There were four main objectives: [1] establish a baseline of trophic ecology for the Arctic charr and sea trout in the Westfjords, [2] estimate trophic overlap for the rainbow trout, and Arctic charr, and the sea trout, [3] attempt to determine the number of escape events for the rainbow trout, and [4] provide management recommendations for the future of the industry. Arctic charr and sea trout were collected throughout the summer of 2017 via gillnets from locations throughout the Westfjords. The stomach contents were analysed and three sets of tissues (liver, muscle, and scale) were taken for stable isotope analysis. Rainbow trout stomach contents data and tissue samples were provided by Fiskistofa and Hafrannsóknastofnun, from fish caught in 2016. A principal components analysis and GLMM was used to compare the stomach contents of the three species. Bayesian standard ellipses and GLMM was used to compare trophic overlap between the three species. K-means cluster analysis was used to determine the number of rainbow trout escape events. Results indicate that there is high trophic overlap between all three species and suggest that most or all of the rainbow trout may have come from one escape event. Management suggestions are focused on preventing futures escapes, and mitigating damage when escapes occur. Fiskieldi er mikilvæg atvinnugrein á Vestfjörðum og regnbogasilungur hefur verið ein af mikilvægustu tegundunum í sjókvíaeldi. Enn hefur ekki enn tekist að koma í veg fyrir að eldisfiskur sleppi úr kvíum og er sjókvíaeldi á Vestfjörðum þar engin undantekning. Markmið þessarrar rannsóknar var ...